Human cytotoxic T lymphocytes against the Plasmodium falciparum circumsporozoite protein. - Malik, A (1991)
Cytotoxic T lymphocytes (CTL) against the circumsporozoite (CS) protein of malaria sporozoites protect against malaria in rodents. Although there is interest in developing human vaccines that induce CTL against the Plasmodium falciparum CS protein, humans have never been shown to produce CTL against any Plasmodium species protein or other parasite protein. We report that when peripheral blood mononuclear cells (PBMC) from three of four volunteers immunized with irradiated P. falciparum sporozoites were stimulated in vitro with a recombinant vaccinia virus expressing the P. falciparum CS protein or a peptide including only amino acids 368-390 of the P. falciparum CS protein [CS-(368-390)], the PBMC lysed autologous Epstein-Barr virus-transformed B cells transfected with the P. falciparum CS protein gene or incubated with CS-(368-390) tricosapeptide. Activity was antigen specific, genetically restricted, and dependent on CD8+ T cells. In one volunteer, seven peptides reflecting amino acids 311-400 were tested, and, as in B10.BR mice, CTL activity was only associated with the CS-(368-390) peptide. Development of an assay for studying human CTL against the CS and other malaria proteins and a method for constructing target cells by direct gene transfection provide a foundation for studying the role of CTL in protection against malaria.